2017
DOI: 10.12973/ejmste/79640
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Land Use Change and Forestation in Response to Demographic Movement and Reduction of Forest Crime

Abstract: The sustainable management of natural resources requires a thorough analysis of the land-use and forest cover dynamics and the effective factors in the changes occurring in them. This study investigated the roles played by social factors in the temporal changes in land cover and deforestation within the Torul State Forest Enterprise in northeastern Turkey. Between 2005 and 2016, this area was examined in terms of forest crime, demographic movement and forest dynamics using the Geographic Information System (GI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…A and Syafinie (2012) found that land use would have a strong impact on local ecosystems through the analysis of land use change, and further analyzed the global greenhouse gas imbalance (Majid and Syafinie, 2012); Chandana et al (2016) used remote sensing index to analyze the wetland cover types in the basin area of northeast India and found that the impact of land use on wetlands will increase with the increase of wetland eutrophication (CHANDANASARMADILIPKUMARDEKA, 2016). Bayramoglu (2018) used aerial photos and remote sensing images to evaluate the impact of land use change on the ecological environment at the landscape scale (Bayramoglu and Kadiogullari, 2018). However, these methods and theories of environmental assessment have more or fewer defects.…”
Section: Research On Environmental Assessment Methodsmentioning
confidence: 99%
“…A and Syafinie (2012) found that land use would have a strong impact on local ecosystems through the analysis of land use change, and further analyzed the global greenhouse gas imbalance (Majid and Syafinie, 2012); Chandana et al (2016) used remote sensing index to analyze the wetland cover types in the basin area of northeast India and found that the impact of land use on wetlands will increase with the increase of wetland eutrophication (CHANDANASARMADILIPKUMARDEKA, 2016). Bayramoglu (2018) used aerial photos and remote sensing images to evaluate the impact of land use change on the ecological environment at the landscape scale (Bayramoglu and Kadiogullari, 2018). However, these methods and theories of environmental assessment have more or fewer defects.…”
Section: Research On Environmental Assessment Methodsmentioning
confidence: 99%
“…(Kementerian Lingkungan Hidup dan Kehutanan RI 2018) At the level of the implicit definition of Forest set by the Central Government, it certainly cannot be ignored that in West Papua Province and specifically in Raja Ampat Regency, it's recognized that indigenous Papuan customary ownership (PCO) is still alive and developing until now, the truth of which cannot be denied by anybody. Several related agencies that have authority over forest crimes (Bayramoglu and Kadiogullari 2018), such as the West Papua Regional Police Police and the Center for Environmental and Forestry Security and Law Enforcement in the Maluku-Papua Region carry out legal procedures and take action regarding forest area land management issues without permission from the Central Government against residents who carry out management land in the forest area and the tail is tried in the Court. (Kristiani 2020) This has also happened concretely in the Alex Robert Womsiwor Criminal Case which was processed by the West Papua Police Police Agency until it was tried at the Class IB Sorong District Court with Criminal Case No: 153/Pid.Sus/2020/PN Son, because of flattening a small portion of the land area of the land area of 1 Ha which is the Land of Parental Inheritance (In-Law) for gardening and coincides with the location of the land which is the Location of Cases (LC) with the status of Non-Productive CPF.…”
Section: Introductionmentioning
confidence: 99%
“…Although land cover changes had occurred in the past, they were mostly a result of natural processes and had little effects on the biosphere (Fanan et al, 2011). Recently, the problem has become complex, fast growing, and mostly caused by human activities (Baral et al, 2018;Bayramoğlu and Kadıoğulları, 2018;Mwangi et al, 2017a;Alemayehu, 2016;Dalil and Nsini, 2014;Mdemu et al, 2012;Misana et al, 2012). The major concern on land cover change has emerged following the massive removal of the natural vegetation by human activities (Kull, 2012;Misana et al, 2012).…”
Section: Introductionmentioning
confidence: 99%